Identification of Arabidopsis Phospholipase A Mutants With Increased Susceptibility to Plasmodiophora brassicae - Zhou, Qinqin; Jayawardhane, Kethmi N.; Strelkov, Stephen E.; Hwang, Sheau-Fang; Chen, Guanqun (Frontiers in Plant Science, 2022)
Clubroot, caused by the obligate parasite Plasmodiophora brassicae, is one of the most devastating diseases of canola (Brassica napus) in Canada. The identification of novel genes that contribute to clubroot resistance is important for the sustainable management of clubroot, as these genes may be used in the development of resistant canola cultivars. Phospholipase As (PLAs) play important roles in plant defense signaling and stress tolerance, and thus are attractive targets for crop breeding. However, since canola is an allopolyploid and has multiple copies of each PLA gene, it is time-consuming to test the functions of PLAs directly in this crop. In contrast, the model plant Arabidopsis thaliana has a simpler genetic background and only one copy of each PLA. Therefore, it would be reasonable and faster to validate the potential utility of PLA genes in Arabidopsis first. In this study, we identified seven homozygous atpla knockout mutants of Arabidopsis, and tested their performance following inoculation with P. brassicae. Four mutants (pla1-iiα, pla1-iγ3, pla1-iii, ppla-iiiβ, ppla-iiiδ) developed more severe clubroot than the wild-type, suggesting increased susceptibility to P. brassicae. The homologs of these AtPLAs in B. napus (BnPLAs) were identified through Blast searches and phylogenic analysis. Expression of the BnPLAs was subsequently examined in transcriptomic datasets generated from canola infected by P. brassicae, and promising candidates for further characterization identified.